1997
DOI: 10.1089/jop.1997.13.261
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclic AMP in Hydrogen Peroxide-Induced Potentiation of Sympathetic Neurotransmission in the Bovine Iris

Abstract: Hydrogen peroxide (H2O2) has been shown to enhance electrically-evoked norepinephrine (NE) release from isolated, superfused bovine irides. Since stimulation of presynaptic adenylyl cyclase can potentiate sympathetic neurotransmission in several tissues, the present study considered the possibility that cyclic AMP may mediate the effects of H2O2 in the iris. Isolated bovine irides were prepared for analysis of field stimulation-induced [3H]NE release using the superfusion method. Both the diterpene activator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The methodology used for the studies on [ 3 H]NE release was similar to that described by Opere and Ohia [25] with minor modifications. Briefly, isolated porcine iris-ciliary bodies (ICBs) were incubated in fresh Krebs solution containing 2.5 lCi/ml [ 3 H]NE at 37°C for 1 h. After incubation, tissues were rinsed twice with non-radioactive buffer for 5 min, mounted between nylon mesh cloths and placed in thermostatically controlled Superfusion Chambers.…”
Section: Studies On [ 3 H]norepinephrine Releasementioning
confidence: 99%
“…The methodology used for the studies on [ 3 H]NE release was similar to that described by Opere and Ohia [25] with minor modifications. Briefly, isolated porcine iris-ciliary bodies (ICBs) were incubated in fresh Krebs solution containing 2.5 lCi/ml [ 3 H]NE at 37°C for 1 h. After incubation, tissues were rinsed twice with non-radioactive buffer for 5 min, mounted between nylon mesh cloths and placed in thermostatically controlled Superfusion Chambers.…”
Section: Studies On [ 3 H]norepinephrine Releasementioning
confidence: 99%
“…Although the mechanism of action is not clear, the authors suggest that intracellular cysteine levels are enhanced indirectly to form GSH by H 2 S stimulation of glutamate/cystine antiporters (Sparatore et al, 2009; Perrino et al, 2009; Osborne et al, 2010). Moreover, as mentioned above, a study by Opere and Ohia (1997) had demonstrated the inhibitory action of H 2 S donors on glutamatergic transmission in mammalian retinae. So, it is plausible that H 2 S donors can render there cytoprotective effects by upregulating system x − C transporter in the retina and thereby increasing the production of glutathione.…”
Section: Regulation Of Transporters By H2s In the Eyementioning
confidence: 84%